2011
DOI: 10.1024/0300-9831/a000067
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidant Vitamin Levels in Patients with Coronary Heart Disease

Abstract: The aim of this study was to investigate anthropometric measurements, body composition, and serum antioxidant vitamin levels in men with coronary heart disease (CHD). Thirty-five men with CHD and 31 men without CHD, aged 40 - 65 years, were included this study. Dietary records and anthropometric measurements of each participant were recorded by researchers and serum antioxidant vitamin levels and lipid profiles were analyzed. Fat mass (FM) and the percentage of fat mass (FM%) in men with CHD was higher than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The results of the study also indicated a highly significant increase in the levels of serum antioxidant Vitamins A and E of patients with IHD and the patient's group without heart disease. Our findings are in agreement with those of other authors who showed serum Vitamin A and Vitamin E levels in patients with chronic heart disease were found to be lower than without heart disease [11][12][13]. On the other hand, some reports indicate that no significant changes occur in patients with heart disease when compare to patients without heart disease [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the study also indicated a highly significant increase in the levels of serum antioxidant Vitamins A and E of patients with IHD and the patient's group without heart disease. Our findings are in agreement with those of other authors who showed serum Vitamin A and Vitamin E levels in patients with chronic heart disease were found to be lower than without heart disease [11][12][13]. On the other hand, some reports indicate that no significant changes occur in patients with heart disease when compare to patients without heart disease [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…According to our searching strategies, we got 24 studies involving a total of 6541 participants, which provided sufficient data for the calculation of difference in α-tocopherol or total tocopherols level between CAD patients and controls. Of these studies, there were 20 case–control studies 15–20, 3043 and four nested case–control studies. 12,4446 There were 15 studies from Asia, 12,15,17,19,20,32,3441,46 seven from Europe, 16,18,30,33,42,43,45 one from Africa 31 and one from North America.…”
Section: Resultsmentioning
confidence: 99%
“…Sex ratio was treated as continuous variable and not available in the study by Yildiran et al. 19 (all male).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study demonstrated significantly a lower serum level of αtocopherol among CAD patients than the control group (Table-4), which agreed with other studies. [18][19][20][21] However, other researchers (Frki, et al (2000) [22] and (Tavallaie, et al (2012) [23] found that there was no statistical difference in the level of vitamin E between CAD and non CAD patients. This low vitamin E could be due to over consumption of antioxidants or low dietary intake.…”
Section: Discussionmentioning
confidence: 99%